A relação executivo-legislativo no plano municipal: uma comparação entre Londrina e Maringá (2013-2016) - Silva, Edmilson Aparecido da (2017)
The relationship between the municipal Executive Power and the municipal Legislative Power become a lot discuss subject in the Brazil scenario, because the way this relationship occurs has an impact on the lives of citizens, especially in the municipal sphere, after all, the political oscillations are verified more quickly when the occurrence is near. Thus, the goal of this work was investigate the relation between the Executive Power and the Legislative Power in the cities of Londrina and Maringá, situated in North of Parana. The methodology adopted was of the descriptive and exploratory type since was realized a documental search about this two Powers of the cities Londrina e Maringá. It was adopted the qualitative approach. The theoretical basis of this work, was made how a review of the literature which searched topics such as: types of presidentialism, forms of accountability and the types of relationships between the Legislative and Executive Powers. The data were collected in the Legislature Houses of the cities of Londrina and Maringá, TSE website, TRE website, news site, newspaper, blogs and other sources. The data collected on the votes in the Legislative Power of the cities studied were treated by the author to obtain the results on the behavior of these Legislative Houses on the votes made during the 2013-2016 legislature. The analysis of these results and the set of other information, allowed to support some conclusions and the main one is that the Executive Powers of the studied cities interfere directly in the agenda of their Legislative Powers, a fact evidenced by the high number of proposals sent by the Executive Power to the Legislative. In both cities the Municipal Ultrapresidentialism was identified, because the Legislative Power votes proposals submitted by the Executive Power, which are approved being the approval percentage reached in Maringá is even higher than that of Londrina. It is also concluded that in the votings Vetos the Legislative Powers behave in defending their autonomy, not allowing it to be threatened by decisions and actions of the Executive Powers, the highlight is also for the Legislative Power of Maringá, which approved a very small number of Vetos appreciated by their. The Legislative Powers of the two cities studied did not fully exercise the role of parliamentary control attributed to them, a fact that was confirmed because no were found records of discussions and tight votes on topics linked, for example, to budgetary oversight. Another interesting fact is the opening of only one Investigation Commission in each of these municipalities, and in addition, the results have been of low impact for the population. Also detected were threats to the autonomy of the Legislative Power, as well as actions to defend this autonomy by that same power.